2018
DOI: 10.18433/jpps29673
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cytochrome P450 (CYP) 2D6 Genetic Polymorphism on the Inhibitory Action of Antidepressants on CYP2D6-Mediated Dopamine Formation from p-Tyramine

Abstract: -PURPOSE: The inhibitory effects of antidepressants, such as imipramine, desipramine, and fluvoxamine, on dopamine formation from p-tyramine catalyzed by cytochrome P450 (CYP) 2D6.2 (Arg296Cys, Ser486Thr) and CYP2D6.10 (Pro34Ser, Ser486Thr), were compared with those on dopamine formation catalyzed by CYP2D6.1 (wild type), to investigate the effect of a CYP2D6 polymorphism on neuroactive amine metabolism in the brain. METHODS: Inhibition constants (Ki) of the antidepressants toward dopamine formation catalyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…However, fluoxetine increased the Km and Vmax values of CYP2D6mediated progesterone 21-hydroxylation (40). Imipramine and desipramine inhibited dopamine formation from p-tyramine and the Ki values for CYP2D6.10 were higher than those for CYP2D6.1 (25). In this study, paroxetine inhibited dopamine formation with a higher Ki value for CYP2D6.10 compared with that for CYP2D6.1.…”
Section: Discussionmentioning
confidence: 42%
See 2 more Smart Citations
“…However, fluoxetine increased the Km and Vmax values of CYP2D6mediated progesterone 21-hydroxylation (40). Imipramine and desipramine inhibited dopamine formation from p-tyramine and the Ki values for CYP2D6.10 were higher than those for CYP2D6.1 (25). In this study, paroxetine inhibited dopamine formation with a higher Ki value for CYP2D6.10 compared with that for CYP2D6.1.…”
Section: Discussionmentioning
confidence: 42%
“…This activation has similarly been demonstrated for other P450s such as CYP1A2, CYP2C8, CYP2C9, CYP2D6, and CYP3A7 (42). We previously observed that fluoxetine increased the Km and Vmax values for CYP2D6-mediated progesterone 21-hydroxylation (40), and that fluvoxamine and other SSRIs increased the Km and Vmax values for dopamine formation mediated by CYP2D6.1, CYP2D6.2, and CYP2D6.10, but decreased the Km value for CYP2D6.10 to the level for CYP2D6.1 and CYP2D6.2 (25). Fluoxetineinduced activation of CYP2D6-mediated progesterone 21-hydroxylation was the first finding in relation to CYP2D6 (40,42).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…For instance, PMs have a greater DA tone in the pituitary gland, combined with a lower serotonin tone, due to serotonin-mediated tonic inhibition [ 74 ]. Overall, the contributions of CYP2D6 and CYP2C19 in the metabolism of endogenous substances are not fully understood, and further investigations are required to prove the physiological implications of CYP450 in the brain [ 69 , 72 , 75 ].…”
Section: The Influence Of Cyp2d6 and Cyp2c19 Variants On Neurotransmi...mentioning
confidence: 99%
“…Sifat Fisikokimia beta-amirin dan stigmasterol Tabel 3 dalam penelitian ini menggambarkan bahwa kedua senyawa tersebut memiliki laju absorpsi yang lambat dengan menganalisis plot boiled-egg (Daina & Zoete, 2016). Beta-amirin merupakan inhibitor dari sitokrom P450 yang berperan sebagai katalis reaksi oksidasi seperti obat eksogen dan karsinogen, ataupun senyawa yang bersifat toksik (Niwa, Yanai, Matsumoto, & Shizuku, 2019). Hal ini menandakan bahwa beta-amirin dapat diproses secara fisiologis oleh enzim sitokrom P450 CYP2C9.…”
Section: Metode Penelitianunclassified